PENGARUH BELANJA MODAL, EKSPOR DAN PERTUMBUHAN EKONOMI TERHADAP TINGKAT KEMISKINAN DI KOTA JAMBI - Anggun Sari, Deby; Helencia, Kiki; Irawan, Deki; Nanda Utami, Febby (JUMANJI (JURNAL MANAJEMEN JAMBI), 2024)
Deby Dkk, 2019 with the title of thesis research, namely the Effects of Capital Expenditures, Exports and Economic Growth on Poverty Levels in Jambi City (Path Analysis Approach) This study aims to: 1) To analyze the effect of Capital Expenditures and Exports on Economic Growth in Jambi City during 2001-2017. 2) To analyze the effect of Capital Expenditures, Exports and Economic Growth on Poverty Levels in Jambi City during 2001-2017. The research model used in this study is the Path Analysis model. The effect of capital expenditure and exports on economic growth in Jambi City during the period of 2001 to 2017 can be concluded that capital expenditure and exports simultaneously influence economic growth in Jambi City. Whereas if viewed partially, the two independent variables, namely capital expenditure, have a negative and significant effect on economic growth and exports have a positive and significant effect on economic growth in Jambi City. The contribution of the direct effect of capital expenditure on economic growth is large and positive in value, but when viewed the contribution of indirect influence on economic growth through exports is greater than the contribution value of direct influence, but the value is negative. Whereas ifcalculated the contribution of the total effect is small and negative for economic growth in Jambi City. The effect of capital expenditure and exports on poverty and economic growth as intervening variables in Jambi City during the period of 2001 to 2017 can be concluded that capital expenditure, exports and economic growth simultaneously have a significant effect on poverty levels in Jambi City. Meanwhile, if viewed partially, only the export variable can have a significant effect on the poverty level, while capital expenditure and economic growth as intervening variables in this analysis model cannot influence the poverty level in Jambi City. Furthermore, testing the Trimming method results in the export variables that have a significant effect on the poverty level. The contribution of the direct effect of the export variable on poverty levels is 47.6 percent